Incidence and Risk Factors of Active Tuberculosis Among Hospitalized Patients with Latent Tuberculosis Infection in China: A Cohort Study - Liu Y; Zhang L; Chen Y; Ruan G; Liu Y; Chen S; Xie L; Wu F; Shi X; Liu X (Infection and Drug Resistance, 2024)
Ye Liu,1,* Lifan Zhang,1– 4,* Yan Chen,1,* Guiren Ruan,1– 3 Yuchen Liu,1 Shi Chen,1 Lantian Xie,1 Fengying Wu,1 Xiaochun Shi,1– 3 Xiaoqing Liu1– 4 1Division of Infectious Diseases, Department of Internal Medicine, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2State Key Laboratory of Complex Severe and Rare Disease, Peking Union Medical College Hospital, Beijing, People’s Republic of China; 3Center for Tuberculosis Research, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 4Clinical Epidemiology Unit, Peking Union Medical College, International Clinical Epidemiology Network, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaochun Shi; Xiaoqing Liu, Division of Infectious Diseases, Department of Internal Medicine, State Key Laboratory of Complex Severe and Rare Disease, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Shuaifuyuan No. 1, Beijing, 100005, People’s Republic of China, Email shixch7722@163.com; liuxq@pumch.cnBackground: The population with latent tuberculosis infection (LTBI) represents a potential pool of patients with active tuberculosis (ATB). T-SPOT.TB is an important test tool for screening LTBI. Owing to the large population of LTBI patients in China, it is necessary to identify a high-risk group for LTBI and enlarge tuberculosis preventive treatment (TPT) to reduce the incidence of ATB.Methods: Hospitalized patients with positive T-SPOT.TB results were recruited from January 2013 to December 2016. Patients with ATB were excluded. Basic information was collected and the development of ATBs was examined during follow-up. The life-table method was used to calculate cumulative incidence rates. Potential risk factors were analyzed through Cox regression analysis.Results: A total of 1680 patients with LTBI were recruited in the follow-up cohort, and 377 (22.44%) patients dropped out. With a median follow-up time of 81 months [interquartile range (IQR):61– 93], 19 of 1303 patients with LTBI developed ATB. The 1-year incidence of ATB was 614 per 100,000 individuals [95%confidence interval (95% CI):584– 644]. Over 5-year period, the cumulative incidence of ATB was 1496 per 100,000 [95% CI:1430– 1570], and the incidence density was 240 per 100,000 person-years[95% CI:144– 375]. In the Cox regression model, exposure of pulmonary tuberculosis (PTB) [adjusted hazard ratio (aHR)=10.557, 95% CI:2.273– 49.031], maximum daily dosage of glucocorticoids (GCs)≥ 50 mg/d (aHR=2.948, 95% CI:1.122– 7.748), leflunomide (LEF) treatment (aHR=8.572, 95% CI:2.222 − 33.070), anemia (aHR=2.565, 95% CI:1.015– 6.479) and T-SPOT.TB level≥ 300SFCs/106 PBMCs (aHR=4.195, 95% CI:1.365– 12.892) were independent risk factors for ATB development in LTBI patients.Conclusion: The incidence of ATB is significantly higher in hospitalized patients with LTBI than in the general population. The exposure history of PTB, maximum daily dosage of GCs≥ 50 mg/day, LEF treatment, anemia, and T-SPOT.TB level≥ 300SFCs/106PBMCs, were the risk factors of tuberculosis reactivation. Hospitalized LTBI patients with the above factors may need TPT.Keywords: latent tuberculosis infection, active tuberculosis, incidence, risk factors